If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 8 = 10x + -6 Reorder the terms: 8 + 4x = 10x + -6 Reorder the terms: 8 + 4x = -6 + 10x Solving 8 + 4x = -6 + 10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10x' to each side of the equation. 8 + 4x + -10x = -6 + 10x + -10x Combine like terms: 4x + -10x = -6x 8 + -6x = -6 + 10x + -10x Combine like terms: 10x + -10x = 0 8 + -6x = -6 + 0 8 + -6x = -6 Add '-8' to each side of the equation. 8 + -8 + -6x = -6 + -8 Combine like terms: 8 + -8 = 0 0 + -6x = -6 + -8 -6x = -6 + -8 Combine like terms: -6 + -8 = -14 -6x = -14 Divide each side by '-6'. x = 2.333333333 Simplifying x = 2.333333333
| 2(2x-9)+5=-7(-x-8) | | y^2-2x=3 | | 4s=n-3m | | 17/4x-1/9=6x | | -1/2-y=0 | | 2+4x+7y= | | 1+5r=2r+8 | | (x-1)(x+2)=-4-x | | (3x-2/3)^2=4.5 | | 13=6c | | f(x)=9-3x^2 | | 10(y+2)=14y-28 | | 14/3x6/7 | | -30+n=5n | | 4^11/2-3=32 | | 1.1=-log(x) | | -2q=-14 | | 3LM-2N=7ON+M | | 6x=3x+3x | | 0.66(h-1)=6h+4+2h | | 4y-4=18-3y | | 65+10m=60m+400 | | 22+11=82+15 | | 0.4(10x+16)=4.5(.2x+5) | | (3x-2/3)^2-2=5/2 | | -2/--4 | | Y-17=83 | | 3n+2n+5n-9= | | X-3/4=8/8 | | 2+5*x=77 | | -10+n=2n | | M/_5=13° |